Assessing horticulture-based land management impacts on carbon dynamics and soil quality - BORDOLOI, JURISANDHYA; BORDOLOI, LAHAR JYOTI; YADAV, KALU RAM; BAISHYA, LOHIT KUMAR (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried during 2020 and 2021 at School of Agricultural Sciences and Rural Development (Nagaland University), Medziphema, Nagaland to study the effects of different horticulture-based land use systems on carbon stock, soil fertility and soil biological health in acidic hill soils of Nagaland. Average values of bulk density of the soils were 1.20 and 1.21 g/cm3 in surface and sub-surface soils, respectively irrespective of type of orchards. The maximum and minimum carbon stock was recorded in pineapple [Ananas comosus (L.) Merr.] (46.77 and 43.38 mg/ha) and citrus (Citrus spp.) (33.07 and 32.42 mg/ha) orchard soils. Soil microbial biomass carbon in pineapple (270.13 and 244.23 µg/g) and citrus orchard soils (165.64 and 152.49 µg/g) was recorded in surface and sub-surface layers, respectively. Banana (Musa spp.) orchard soils had greater values of dehydrogenase activity (15.26 and 9.83 µg TPF/g/h). Soils of banana orchard also recorded highest acid phosphatase activity (176.0 and 165.5 µg PNP/g/h), which was at par with mango (Mangifera indica L.) orchard soils (175 and 166 µg PNP/g/h). Minimum acid phosphatase activity (162.0 and 150.0 µg PNP/g/h) was recorded in citrus orchard soils. Maximum earthworm population density was recorded in banana orchard (12–20 number/m2) and minimum (4–12 number/m2) in citrus orchards.